Robust tracking control of kinematically redundant robot manipulators subject to multiple self-motion criteria [3] - Zergero?lu, Erkan; Şahin, Türker; Özbay, Ufuk; Tektaş, Ümit Ali (My University, 2007)
In this study, we consider a model based robust control scheme for kinematically redundant robot manipulators that also enables the use of self motion of the manipulator to perform multiple sub-tasks (like, maintaining manipulability, avoidance of mechanical joint limits and obstacle avoidance). The controller proposed ensures uniformly ultimately bounded end-effector and sub-task tracking despite the parametric uncertainty associated with the dynamic model. The controller design has been based on a Lyapunov type approach. Simulation results performed on a 3 link planar robot arm are presented to demonstrate the capabilities and the performance of the controller. ©2006 IEEE. © 2011 Elsevier B.V., All rights reserved.
Joint 2006 IEEE Conference on Control Applications (CCA), Computer-Aided Control Systems Design Symposium (CACSD) and International Symposium on Intelligent Control (ISIC) -- Munich -- 71980
Keywords: Redundant robot manipulators; Robust tracking control; Self-motion criteria; Dynamic models; Motion control; Position control; Robots; Redundant manipulators